Budidaya Tanaman Agloenema (Agloenema sp) - Anastasia H.P. Enga; Maria Alfonsa Ngaku; Agnes Yunita Dea (Abdibaraya, 2026)
Aglaonema cultivation is relatively easy to do because this plant is known to grow easily. The things that need to be considered in Aglaonema cultivation are light, humidity, and growing media. Aglaonema plants are cultivated at the Flores Bajawa Agricultural College. Of course, this cultivation is a practical industrial work activity for students in Komba City. Aglaonema plants are cultivated at the Flores Bajawa Agricultural College. The purpose of this activity is to learn about the process of cultivating aglaonema plants. Methods of identification and cultivation of ornamental plants. The results obtained during this industrial work practice are that there are five types of aglaonema plants cultivated at the Flores Bajawa Agricultural College, namely Aglaonema Harlequin, BJ Freeman, Sri Rejeki Super White, Claudia, and Anyamanee. Plant height and number of leaves vary according to the age of the plant. The number of aglaonema plants cultivated at the Flores Bajawa Agricultural College during the industrial work practice was ten pots.